Compositions of the essential oils from two types of ocimum basilicum introduced in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2013)
Essential oils from two types of Ocimum basilicum introduced in Bangladesh were analyzed by GC-MS. The major constituents found in the oil collected from Indian variety were methyl chavicol (78.2), citral (3.7%) and tau-cadinol (2.49%). Introduced variety from Thailand contains anisole, p-propenyl (93.99%) as major compound. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17335 Bangladesh J. Sci. Ind. Res. 48(3), 217-220, 2013